2007
DOI: 10.1016/j.bmc.2006.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the active site of phenylethanolamine N-methyltransferase with 1,2,3,4-tetrahydrobenz[h]isoquinoline inhibitors☆

Abstract: 1,2,3,isoquinoline (THBQ, 11) is a potent, inhibitor of phenylethanolamine Nmethyltransferase (PNMT). Docking studies indicated that the enhanced PNMT inhibitory potency of 11 (hPNMT K i = 0.49 μM) versus 1,2,3,4-tetrahydroisoquinoline (5, hPNMT K i = 5.8 μM) was likely due to hydrophobic interactions with Val53, Met258, Val272, and Val269 in the PNMT active site. These studies also suggested that the addition of substituents to the 7-position of 11 that are capable of forming hydrogen bonds to the enzyme coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Such pseudo-halides, however, cannot be used as precursors for the generation of free radicals or organometallic reagents . Traditional methods for the synthesis of aryl halides (bromides or chlorides) from phenols require either forcing conditions or multi-step procedures . Herein, we report the first example of palladium-catalyzed direct conversion of readily available aryl sulfonate esters to aryl bromides and chlorides.…”
mentioning
confidence: 99%
“…Such pseudo-halides, however, cannot be used as precursors for the generation of free radicals or organometallic reagents . Traditional methods for the synthesis of aryl halides (bromides or chlorides) from phenols require either forcing conditions or multi-step procedures . Herein, we report the first example of palladium-catalyzed direct conversion of readily available aryl sulfonate esters to aryl bromides and chlorides.…”
mentioning
confidence: 99%
“…Two different hPNMT inhibitors, 1 and 2, have been reported to inhibit the enzyme with K i values of 0.28 μM and 0.063 μM, respectively (radiochemical assay). 52 It has been shown that these two ligands bind to different conformations of the hPNMT binding site (Figure 6A). Both compounds engage in significant hydrophobic interactions, but the larger ligand (2) positions a p-chlorophenyl group in a cavity that is hidden in the hPNMT/1 complex.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 99%
“…However, all compounds synthesised were actually less active than the parent H-substituted analogue. The authors suggest that this illustrates that there are limitations to the extent to which predictions based on docking studies can be employed to guide chemistry [66].…”
Section: The Crystallisation Conditions Are Relevant For Drug Designmentioning
confidence: 99%